Intake, Energy Expenditure and Methane Emissions of Grazing Dairy Cows at Two Pre-Grazing Herbage Masses - Loza, Cecilia (2021)
A grazing experiment was undertaken to assess the effects of two levels of herbage mass (HM) on herbage DM intake (DMI), fat and protein corrected milk yield (FPCM), grazing behaviour, energy expenditure (HP), and methane emissions (CH4) of grazing dairy cows in spring. Treatments were a low HM (1447 kg DM/ha; LHM) or a high HM (1859 kg DM/ha; HHM). Pasture was composed mainly of cocksfoot (Dactylis glomerata) and lucerne (Medicago sativa), offered at a daily herbage allowance of 30 kg DM/cow, above 5 cm. Eight multiparous Holstein cows were used in a 2 × 2 Latin Square design in two 10-day periods. Despite the differences in pre-grazing HM between treatments, OM digestibility was not different (P = 0.28). Herbage mass did not affect DMI or FPCM. Grazing time was not different between treatments, but cows had a greater bite rate when grazing on LHM swards. However, HP did not differ between treatments. Daily methane emission (per cow), methane emission intensity (per kg FPCM) and methane yield (as percentage of gross energy intake) were not different. The lack of effect of the amount of pre-grazing HM on energy intake, confirms that the difference between HM treatments was beyond the limits that impose extra energy expenditure during grazing.